STUDENTS’ PERCEPTIONS TOWARD THE USE OF TEXTBOOK AS LEARNING MEDIA IN LEARNING ENGLISH - Pramudya, Arfan Seina (ENGLISH RESEARCH JOURNAL, 2025)
The research studies about Students’ Perceptions Toward the Use of Textbook as Learning Media in Learning English for the Second Grade Students of SMP N 15 Surakarta. The problem in this study are about what is perceptions students about used of new textbook as learning media in English learning. It is important to know students' perceptions of the textbooks they use. This study is used descriptive qualitative research. The subjects of the research are the class in second grade students of SMP 15 Surakarta in academic year 2023/2024. Each class consist of 29 students. The data was collected through questionnaire and interview. Student perception data were analyzed by collecting data, reducing data, presenting data, and drawing conclusions. For validating of data, researchers used triangulation of methods and sources. In analyzing data, researchers used data condensation, data presentation, and drawing and verifying conclusions. The results of this research show that were: Positive perceptions conveyed by students toward to the teaching materials: have a real impact, interesting materials learning, encourage students, , pay attention to student readiness, authentic, communicative, provide opportunities for feedback on results. Students' give a neutral perceptions toward to the materials about  help students feel comfortable, useful and relevant , do not meet students with different learning styles, the book  present a pleasent views, ilustration are not present clearly, present an interesting image, do not maximize students' learning potential. Based on interviews with several students, it also shows positive perceptions and is in accordance with the results of the questionnaire questions. In accordance with Tomlison's theory, this book has positive observation results in accordance with standard criteria, although there are many who are neutral, but the majority do not have negative perceptions. Keyword perception, textbook, learning media